Network effects, homogeneous goods and international currency choice: new evidence on oil markets from an older era - Barry Eichengreen; Livia Chiţu; Arnaud Mehl (European Central Bank (ECB), 2014)
Conventional wisdom has it that network effects are strong in markets for homogeneous goods, leading to the dominance of one settlement currency in such markets. The alleged dominance of the dollar in global oil markets is said to epitomize this phenomenon. We question this presumption with evidence for earlier periods showing that several national currencies have simultaneously played substantial roles in global oil markets. European oil import payments before and after World War II were split between the dollar and non-dollar currencies, mainly sterling. Differences in use of the dollar across countries were associated with trade linkages with the United States and the size of the importing country. That several national currencies could simultaneously play a role in international oil settlements suggests that a shift from the current dollar-based system toward a multi-polar system in the period ahead is not impossible.
Keywords: F30; N20; 330; homogeneous goods; international invoicing currency; network effects; oil markets; US dollar role